Body: an ambiguous sort of being. Approach toward philosophy of body in Merleau-Ponty’s phenomenology (2011)
This work is an approximation to the philosophy of body starting from Maurice Merleau-Ponty’s Phenomenology of Perception. Based on the concept of phenomenal body, we find a conception of body depicted as an ambiguous sort of being. The following sections